Evaluation of unified intensity-modulated arc therapy for the radiotherapy of head-and-neck cancer. Issue 2 (May 2016) - MacFarlane, Michael; Hoover, Douglas A.; Wong, Eugene; Read, Nancy; Palma, David; Venkatesan, Varagur; Hammond, Alex; Battista, Jerry J.; Chen, Jeff Z.
Abstract: Purpose: Recently our group developed a unified intensity-modulated arc therapy (UIMAT) technique which allows for the simultaneous inverse-optimization and the combined delivery of volume-modulated arc therapy (VMAT) and intensity-modulated radiation therapy (IMRT). The aim of this study was to evaluate the dosimetric benefits of UIMAT plans for radiation treatment of complex head-and-neck cancer cases. Methods and materials: A retrospective treatment planning study was performed on 30 head-and-neck cases, 15 of which were treated clinically with VMAT while the other 15 were treated with step-and-shoot IMRT. These cases were re-planned using our UIMAT technique and the results were compared with the clinically delivered plans. Plans were assessed in terms of clinically relevant metrics describing target volume coverage, dose conformity, and the sparing of organs at risk. Results: When compared to stand-alone VMAT or IMRT, UIMAT plans offered slightly better tumor volume coverage (Median D95: 98.1% vs. 97.5%, p  = 0.01) and similar dose conformity (Median CI: 0.69 vs. 0.69, p  = 0.09). More significantly, UIMAT plans had substantially lower doses to all organs at risk, including the spinal cord (Median D 2% : 29.9 Gy vs. 35.6 Gy, p  < 0.01), brainstem (Median D 2% : 21.2 Gy vs. 25.6 Gy, p  < 0.01), left parotid (Median D Mean : 26.1 Gy vs. 28.0 Gy, p  < 0.01), and right parotid (Median D Mean : 23.6 Gy vs. 27.2 Gy, p  < 0.01). The reduction in OAR doses did not result from the redistribution of dose to unspecified tissue. Furthermore, UIMAT plans can be delivered with comparable delivery times to VMAT (Median time: 135 s vs. 168 s, p  = 0.394) but with fewer monitor units (Median MU: 486 vs. 635, p  < 0.01). Conclusions: Compared to stand-alone IMRT or VMAT, UIMAT was demonstrated to have a dosimetric advantage for the radiation treatment of head-and-neck cancer.